A Web Based Expert System for Identifying Bloomed Plants - Anny Kartika Sari; Adriana Sari Aryani (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2006)
This research discusses the development of a web based expert system for identifying bloomed plants. The identification is based on the seven visible features of a bloomed plant, i.e. the root type, the type of the plant, the shape of the flowers, the shape of the leaves, the height of the plant, and the length and the width of the leaves. For inference process, the forward chaining method is used. The system is developed using PHP as the programming language and MySQL as the database management system. Based on some testing conducted to the system, it can be concluded that the system can identify bloomed plants with the accuracy of 100%. The system can accommodate the update on its knowledge as long as the update is only on the available features in the system. This drawback can be used as starting point for the future development of the system.